(untitled) (Economic and Political Thought, 2013)
Open Pension Schemes in Poland (OFE) result from the privatization of the pension system implemented in response to the World Bank demands. The privatization of this kind has been implemented only in a few countries in the world, in Latin America, Asia and East-Central Europe. Practically, it turned out that the existence of an obligatory capital pillar became the main source of public debt and as a result a threat to the stability of public finance. In Poland, since 1999, half of the increase in public debt has been caused by OFE. The continuation of the obligatory capital pillar maintenance will result in the necessity to raise taxes and reduce important public spending. Financing OFE by increasing public debt may become impossible because of the precautionary public debt thresholds specified in the Act on Public Finance and the Constitution. Additional limitations result from the necessity to undertake action indispensable in order to make the Council of the European Union lift the procedure of excessive deficit imposed on Poland in 2009.